(untitled) (Fiep Bulletin - online, 2019)
Brazil has been undergoing an aging process and the search for physical exercise in programs for health promotion hasbeen increasing. The general objective of the present research was to verify the aspects that motivate the elderly to practice physicalexercises in gymnasiums in the city of Caicó - RN. The sample consisted of 30 elderly people, who answered a semi-structuredquestionnaire. Descriptive research with standardized techniques of data collection, questionnaire and systematic observation,Survey and quantitative approach. The data obtained were quantitatively analyzed for data tabulation using the Microsoft Excelspreadsheet, the results indicate that the greatest motivation was the pursuit of health (70%), followed by the pursuit of leisure (24%),followed by the improvement of psychological issues and by the question of aesthetics (3%). Factor that draws attention is that none ofthem was motivated by physical conditioning. Considering that the practice of physical activity is an important factor for a healthyaging, it is suggested that some measures be adopted by the public power and other institutions so that a more active lifestyle is morepresent in the daily life of the elderly and that studies with greater number are performed.